Home away from home The sharing economy and visitors to Iceland - Jónsson, Örn D.; Huijbens, Edward H. (School of Social Sciences, 2023)
This article discusses issues of contention in the development of the sharing economy world-wide and contextualises these in Icelandic tourism development. The article describes the key concepts, premises and functioning of the sharing economy and how these can facilitate entrepreneurship in tourism to the enhancement of human capital and innovation. At the same time the article warns of a more sinister side to the sharing economy as it is about monetizing community relationships and could consequently undermine these and accepted codes of conduct. In addition, once infrastructure is being deliberately purchased for purposes of sharing, communities become hollowed out. No strong evidence exists in Iceland of this sinister side to the sharing economy, thus the article argues that growing tourism in Iceland has the opportunity to seize the positive aspects of the sharing economy if policy is informed and formulated accordingly. The aim of the article is to explain how growing tourism can increase opportunities in the industry through changing learning processes of innovation and creating chances for people to direct their own daily lives. Greinin snýst um að draga fram álitamál í tengslum við þróun deilihagkerfisins í heiminum í samhengi íslenskrar ferðaþjónustu. Í henni er leitast við að skýra lykilhugtök, forsendur og virkni deilihagkerfisins og hvernig það getur örvað frumkvöðlastarf í ferðaþjónustu og eflt mannauð og nýsköpun. Á sama tíma er varað við skuggahliðum deilihagkerfisins þar sem fjárvæðing tengsla nærsamfélagsins getur grafið undan viðmiðum og leikreglum þess, auk þess sem uppkaup framleiðsluinnviða í þágu deilingar leiða til rýrnandi samfélagsgæða. Ekki eru sterkar vísbendingar um þessar skuggahliðar í íslensku samfélagi en greinin leiðir að því líkum að ör fjölgun gesta hingað til lands bjóði enn sem komið er tækifæri til að virkja kosti deilihagkerfisins ef rétt er á stefnumótun haldið. Markmið greinarinnar er að skýra hvernig horfa má á fjölgun ferðamanna út frá því hvernig hún eflir ...